Pengaruh Bee Pollen Terhadap Daya Terima dan Kandungan Zat Gizi Dalam Pembuatan Crackers - Fatimah Fitriani Mujahidah (Jurnal Ilmiah Kesehatan (JIKA), 2020)
Toddler nutrition problems are directly related to the quantity and quality of food they consume. The research aimed to obtain crackers products that contain amino acids and iron with substitution of bee pollen (bee pollen) flour for the toddler. The type of research used is a quasi-experimental design with laboratory analysis. The research was carried out in three stages: the first stage was an introductory research with laboratory tests on bee pollen flour and organoleptic test, the second stage was the product initial research, and the third stage proximate analysis was conducted, amino acid content, and iron suit of SNI. In the main research was the process of making crackers with the formula 25%,75%,100% and done by 20 panelists. The research result of crackers formula C2 gave the good preference level. For the product initial research was the proximate analysis, the selected formulas was 7,74% protein, 22,81% fat, 63,61% carbohydrates, 3,36% water content, and 2,52% ash content. Fe content in bee pollen flour was 145,7862 ppm after being processed into crackers at 88.4402 ppm. The bee polen flour has a good acceptability and nutrient content, although the iron content has decreased after being processed into crackers, this is due to the high temperature used when the crackers are baked.